2005
DOI: 10.1051/0004-6361:20040519
|View full text |Cite
|
Sign up to set email alerts
|

Pulsation of the K 2.5 giant star GSC 09137-03505?

Abstract: Abstract. In July, 1999, the Hubble Space Telescope (HST) pointed for more than 8 days continuously at the globular cluster 47 Tucanae. Two guide stars were used during this campaign by the Fine Guidance Sensors (FGS). Using more than 19 million photometric FGS data for the guide star GSC 09137-03505 we found brightness variability corresponding to three approximately equidistant frequencies. The detected frequencies range from 21 to 71 µHz with amplitudes between 341 and 291 ppm. Multicolor CCD photometry was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…The Fourier spectrum shows the highest amplitude at 6.51 d −1 , whereas maximum significance is obtained at 6.485 d −1 . Recent measurements (Kallinger & Zwintz, 2004) confirm the SigSpec result.…”
Section: Which Alias?supporting
confidence: 58%
See 2 more Smart Citations
“…The Fourier spectrum shows the highest amplitude at 6.51 d −1 , whereas maximum significance is obtained at 6.485 d −1 . Recent measurements (Kallinger & Zwintz, 2004) confirm the SigSpec result.…”
Section: Which Alias?supporting
confidence: 58%
“…On the other hand, measurements of the HST-FGS on GSC 09137-03505 (Kallinger et al 2004) provide complementary results. Fourier analysis, S/N estimation, and consecutive prewhitening return three significant components, whereas SigSpec provides 37 frequencies.…”
Section: Underestimation Of Significance By S/nmentioning
confidence: 99%
See 1 more Smart Citation
“…Kallinger et al (2008a) found 16 and 20 pulsation frequencies for V 588 Mon and V 589 Mon, respectively, based on observations obtained during a ground based multi-site campaign. The two PMS pulsators were also observed repeatedly using the MOST satellite (Kallinger et al 2009), where many more pulsation frequencies were identified and studied asteroseismologically.…”
Section: The Young Open Cluster Ngc 2264mentioning
confidence: 99%
“…Examples include the G9.5 giant Oph, based on radial velocities from the CORALIE and ELODIE spectrographs and Fabry Imaging photometry from the MOST satellite (Barban et al 2007), and the G7 giant ξ Hya, based on radial velocity measurements with the CORALIE spectrograph (Frandsen et al 2002), or the K2.5 giant star GSC 09137-03505 where Kallinger et al (2005) found oscillations, based on Fine Guidance Sensor photometry by the Hubble Space Telescope.…”
Section: Introductionmentioning
confidence: 99%